Anxiety, subjective cognitive decline, and cortical amyloid in preclinical autosomal dominant alzheimer's disease: a preliminary report (2017)
Background: Neuropsychiatric symptoms (NPS) often emerge in early stages of Alzheimer’s disease (AD), with anxiety being one of the earliest. Despite this, the relationship between anxiety and AD pathology (e.g. amyloid and tau aggregation) is not well understood. Also of interest is the relation between anxiety in early AD and subjective cognitive decline (SCD). Studying these relationships in carriers of an AD-causing mutation (PSEN-1 E280A) from the Colombian kindred of early-onset autosomal-dominant AD (EOAD) presents the unique opportunity to isolate effects of AD pathology in NPS onset, independent from cerebrovascular disease and other age-associated co-morbidities. Methods: We administered the Geriatric Anxiety Inventory to twenty-one cognitively normal subjects (28-42 years old) from the Colombian kindred: ten mutation carriers and eleven age-matched non-carriers. All subjects had one parent with the PSEN-1 mutation, and thus bore a 50% risk of carrying it themselves; all were blind to their genetic status. All subjects underwent amyloid (Pittsburgh Compound B) and tau (Flortaucipir a.k.a AV-1451) PET imaging. SCD was measured using the Memory Complaint Scale-Spanish version. Pearson correlations were used to compare anxiety, SCD, cortical amyloid, and regional tau levels in inferior temporal lobe (IT) and entorhinal cortex (EC). Results: In PSEN-1 carriers, greater anxiety was associated with greater cortical amyloid (r=0.817, p=0.004), but not with tau (IT: r=-0.007, p=0.985; EC: r=0.036, p=0.921). Greater SCD (self and informant) was also associated with greater cortical amyloid (self: r=0.902, p=0.001), but not tau (IT: r=0.076, p=0.846; EC: r=0.018, p=0.963). There were no differences between mutation carriers and non-carriers in anxiety (p=0.911) or SCD (self: p=0.848; informant: p=0.614). Among mutation carriers, greater anxiety was associated with greater SCD (self: r=0.957; p<0.001; informant: r=0.932; p<0.001). Conclusions: Preliminary findings support a relationship between anxiety, SCD, and amyloid (but not tau), among mutation carriers from the Colombian kindred of EOAD. Results suggest that anxiety in this cohort is redundant with SCD, and related to early changes in AD biomarkers, years before the estimated onset of mild cognitive impairment. Future longitudinal studies with larger samples and in relation to objective cognitive measures are needed to better understand anxiety and SCD in preclinical AD.